Some Strong Logics Within Combinatorial Set Theory and the Logic of Chains - Džamonja, Mirna; Väänänen, Jouko (Sarajevo Journal of Mathematics, 2019)
In this note we report on a project in progress, where we study compactness of infinitary logics, including the logic of chains. The motivation of this project is to find logical reasons for the set-theoretic phenomenon of compactness at singular cardinals.